Implementation of Strategic Management in Islamic Leadership to Improve Teacher Performance - Yuli Supriani; Dian Eka Priyantoro; Muhammad Yusuf (The Nexus Journal of Education, Management, and Entrepreneurship, 2026)
Improving teacher performance is a crucial factor in enhancing the quality of Islamic education in madrasah aliyah. However, several challenges remain, including the lack of well-directed managerial strategies and the inconsistent implementation of Islamic leadership values, which affect the effectiveness of learning. This study aims to analyze the implementation of strategic management based on Islamic leadership and its influence on teacher performance at MA Mamba’ul Ulum Metro. This research employed a descriptive qualitative method involving teachers and the head of the madrasah as research subjects. Data were collected through semi-structured interviews, participatory observation, and institutional documentation, and were then analyzed thematically. The findings indicate that participatory strategic planning, Islamic leadership that emphasizes trustworthiness (amanah) and consultation (musyawarah), and performance evaluation based on clear indicators substantially improve teachers’ motivation, professionalism, and creativity. The integration of managerial strategies and moral values creates a harmonious work environment and supports pedagogical innovation. This study concludes that strategic management based on Islamic leadership can serve as a model for madrasahs to improve teacher performance and the quality of education. It also provides a basis for further research on the impact of this strategy on students’ academic achievement and character development.